Ethnomedicinal Plants used for curing various Skin diseases in Shopian district of Jammu and Kashmir. - Khanday, Zakir Hussain; Singh, Sumer (Journal of Phytology, 2017)
Medicinal plants are used by tribals& local people in shopian (j&k) in the treatment of various skin diseases, like dandruff, rash hairfall, Dermatitis etc. Traditional methods of disease treatment using medicinal plant is predominant among rural & tribal communities of shopian Kashmir. The district shopian has a rich flora of medicinal plants with diverse biological properties. Ethnomedicinal survey with respect to use of local medicinal plants for curing skin problems was carried out during the summer seasons of 2015-2016. Present investigation reveals that 25 Ethnomedicinal plant species belonging to 21 families are being commonly used for skin diseases. An inventory of traditional knowledge about medicinal plants used in skin diseases by local & tribal people as home remedies/ folk medicine has been complied.Â 